Creating public value in global wicked problems. Issue 5 (28th May 2017) - Geuijen, Karin; Moore, Mark; Cederquist, Andrea; Ronning, Rolf; van Twist, Mark
ABSTRACT: This essay seeks to explore in which way Public Value Theory (PVT) would be useful in guiding analysis and action with respect to global wicked issues like forced migration. We found that (1) PVT enables envisioning global, collective, public value as well as value for individuals, communities and states by including voices of 'all affected interests' even when discourses prove to be extremely conflicting; (2) PVT enables acknowledging collaborative innovation as a possible means of facilitating cross-sectoral and local – global (transnational) connections which might help reframing wicked global issues and delivering results; (3) When PVT is applied to global wicked issues it offers an opportunity to explore which kind of institutional innovation is required to convene an appropriate authorizing structure in the 'institutional void' at the transnational level. Requisite adjustments to PVT are identified.